Effects of magnesium sulfate on airway smooth muscle contraction in rats - Hatice Betul Altinisik; Pakize Kirdemir; Ugur Altinisik; Osman Gokalp (Medicinski glasnik, 2016)
Aim: To investigate the effect of magnesium sulfate (MgSO4) at different doses on isolated tracheal smooth muscle contraction in rats induced by different mechanisms. Methods: Twelve rats’ tracheas were placed into organ bath. Consecutively, acetylcholine (10−6,10−5,10−4 M), histamine (10−8,10−5,10−3 M) and KCl (30,60 mM) solutions was administered for contractions. MgSO4 from 10−4 to 10−1 M concentrations were subsequently administered after each constrictive agent and relaxation degrees were recorded. Results: In the acetylcholine and KCl groups, dose dependent strong contractions were observed, but not in the histamine group and that group was excluded. Significant relaxation occurred with gradually increasing doses of MgSO4. In the high dose KCl group, a slight increase in contractions after the administration of 10−4 and 10−3 M MgSO4 was recorded. Conclusion: We suggest that MgSO4 is effective in relaxing airway smooth muscle contractions caused by different factors; however, it must be considered that low doses of MgSO4 may only lead to a slight increase in contractions.
Keywords: acetylcholine; histamine; potassium chloride